2013
DOI: 10.3393/ac.2013.29.2.77
|View full text |Cite
|
Sign up to set email alerts
|

A Stercoral Perforation of the Rectum

Abstract: A stercoral perforation of the rectum due to a fecaloma is a rare disease with a high mortality rate. Although multiple case reports of colonic perforations have been published, the data regarding rectal perforations are limited. This case report will highlight one such case of a stercoral rectal perforation that was successfully treated with a laparoscopic operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 10 publications
(12 reference statements)
0
20
0
Order By: Relevance
“…8 It is a somewhat ''rare'' phenomenon, with stercoral perforation of the terminal ileum, cecum and rectum being an even less common phenomenon. 8,10,11 Thus, Serpell and Nicholls 8 reviewed the literature from 1894 (date of the first recorded case 12 ) to 1990 and identified a total of 64 cases. Similarly, Maurer et al 9 reviewed the literature from 1894 to 1998 and identified a total of 81 cases, although they also reported a further seven cases managed in their unit in the preceding five-year period.…”
Section: Discussionmentioning
confidence: 99%
“…8 It is a somewhat ''rare'' phenomenon, with stercoral perforation of the terminal ileum, cecum and rectum being an even less common phenomenon. 8,10,11 Thus, Serpell and Nicholls 8 reviewed the literature from 1894 (date of the first recorded case 12 ) to 1990 and identified a total of 64 cases. Similarly, Maurer et al 9 reviewed the literature from 1894 to 1998 and identified a total of 81 cases, although they also reported a further seven cases managed in their unit in the preceding five-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Stercoral perforation due to faecaloma causing pressure-induced ischemic necrosis of the bowel wall was also reported [ 8 ]. Therefore, colonic perforations in spinal cord injury patients were mainly related to stercoral perforation, digital evacuation of feces, and insertion of enemas [ 9 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with fecal impaction, CT scans may reveal the presence of stercoral colitis. Chest x-rays may only reveal free air under the diaphragm in 30% of cases of colonic perforation [14]. In uncomplicated fecal impaction, there is colonic distension, and the wall is thin; however, in stercoral ulceration, focal thickening of the colonic wall may be present caused by edema from the ischemia and ulceration.…”
Section: Discussionmentioning
confidence: 99%